Importance of institutional quality and technological innovation to achieve sustainable energy goal: Fresh policy insights - Leilei Zhang; Kashif Raza Abbasi; Khadim Hussain; Mohammed Awad Abuhussain; Ali Aldersoni; Rafael Alvarado (Journal of Innovation & Knowledge (JIK), 2023)
Globally, energy is considered a backbone for any country's sustainable growth. However, Pakistan has still encountered a massive energy crisis that affects its society economically. Therefore, policymakers keenly focused on distinguishing factors contributing to Pakistan's sustainable energy plan in the current scenario. Given the importance, it is vital to examine technological innovation, institutional quality, public-private partnerships in energy, and GDP with electricity consumption from 1980 to 2019. The study uses novel dynamic ARDL simulations, and Cumulative Fourier Frequency Domain Causality (CFFDC) approaches for empirical estimation. The findings show that GDP and institutional quality have an affirmative short- and long-run effect on energy consumption. On the other hand, technological innovation has a long-term positive influence on electricity consumption. In contrast, public-private partnerships in energy were found insignificant. The outcomes suggest that technological innovation, institutional quality, and GDP are the most effective determinants and have the greatest effect on energy consumption. Other problems must be addressed, such as pervasive corruption and bureaucratic complexities, underdeveloped grids, and insufficient resource management.
Keywords: Q47; 650; DARDL; Energy consumption; Institutional quality; Technological innovation